Chemical Evaluation Of Tamra Bhasma - DR. KANCHAN S. CHITNIS,; MISS. ASHLEY STANLEY, (International Journal of Pharma and Bio Sciences, 2011)
Bhasmas are traditional Indian medicinal preparations in which metals undergo thermal treatment process to bring about thermal decomposition, phase transition, purification, detoxification and their conversion into a digestible oxide or sulfide form. Tamra Bhasma is copper bhasma. The present experiment was done to estimate the amount of copper present in Tamra Bhasma of different batches, different manufacturers and formulations containing Tamra Bhasma by Atomic Absorption Spectroscopy. Spectrophotometric and X- Ray Diffraction analysis were also performed on the samples. It was seen that samples from different batches and different manufacturers contained varying amounts of Tamra Bhasma. Spectrophotometric analysis showed that copper was present predominantly in its cupric state. X- Ray Diffraction analysis showed that the copper in the bhasma was present in its sulphide form. Analysis of formulations showed variations in the copper content from the label claim. The results from the study stress the need for use of modern analytical tools for standardization and evaluation of traditional medicines.